Effect of Biochar Application on Physicochemical and Hydraulic Properties of Loess - Xiujuan Yang; Henghui Fan; Yuhang Du; Lu Zhang (Advances in Civil Engineering)
Biochar is important for optimizing soil physical structure and improving soil water retention. The saturated water capacity test, water repellency test, and permeability coefficient test were used to study the effects of biochar additive amount (0, 2, 5, 10, 15, and 20 g/kg) and particle size (>2 mm, 2 mm–0.075 mm, and <0.075 mm) on the basic physicochemical and hydraulic properties of loess. The results showed that with the increase of biochar additive content, the relative particle density decreased linearly (R2 = 0.984); the plastic limit, liquid limit, and plasticity index increased (R2 = 0.947, 0.991, and 0.984, respectively); the maximum dry density decreased (R2 = 0.900); and the optimal water content and saturated water content increased gradually. At the same time, the soil’s pH increased (R2 = 0.957), the soil water repellency decreased, and the water infiltration became easier, but the soil’s permeability coefficient (saturated water conductivity) decreased. When the the biochar particles size is smaller, the soil’s water repellency and permeability coefficient reduced. Studies had shown that the application of biochar makes the loess infiltrate easily, seepage slowly, and contain more water, which improve the water infiltration characteristics and water retention capacity of loess.